Empirical Models of foF2 and hmF2 Reconstituted by Global Ionosonde and Reanalysis Data and COSMIC Observations - Fuqing Huang; Haibing Ruan; Jiuhou Lei; Jiahao Zhong; Xinan Yue; Guozhu Li; Yiding Chen; Jianhui He; Na Li; Xiaoli Luan; Chao Xiong; Xiankang Dou (Space Weather)
Abstract The F2‐peak plasma frequency (foF2) and the height of the F2 peak (hmF2) are two of the most important parameters for any ionospheric model, as well as radio propagation studies and applications. In this study, we have developed empirical models to capture the most significant variations of foF2 and hmF2. The derived empirical models (referred to as the USTC models within this study) are specified through global ionosonde and reanalysis data based on the International Reference Ionosphere (IRI) Consultative Committee on International Radio (CCIR) method and Constellation Observindg System for Meteorology, Ionosphere, and Climate (COSMIC) observations based on the empirical orthogonal function analysis, respectively. The USTC models are validated against the IRI CCIR model prediction. The comparison results revealed that the empirical foF2 model performs better in capturing the foF2 variations than the IRI CCIR model, which can overcome the underestimation of the IRI CCIR model at low latitudes. Although the IRI CCIR model overestimation at middle latitudes is addressed by the empirical hmF2 model, the visible differences between the model predictions and ionosonde observations still exist at low latitudes, which could be attributed to the significant difference between COSMIC and ionosonde hmF2 measures.